Digital systems design using VHDL - Roth, Charles H.; John, Lizy Kurian (Cengage Learning, 2018)
Learn how to effectively use the industry-standard hardware description language, VHDL, as this book integrates VHDL into the digital design process. The book begins with a valuable review of basic logic design concepts before introducing the fundamentals of VHDL. The book concludes with detailed coverage of advanced VHDL topic